Adverse Events at Baseline in a Chinese General Hospital: A Pilot Study of the Global Trigger Tool. Issue 4 (December 2020) - Xu, Xiao-Di; Yuan, Yi-Jie; Zhao, Li-Ming; Li, Yang; Zhang, Hui-Zhen; Wu, Hua
Abstract : Objective: To investigate adverse events (AEs) at baseline in a Chinese general hospital using the Institute for Healthcare Improvement (IHI) Global Trigger Tool (GTT) and discuss the feasibility of this tool to detect AEs in China. Methods: A total of 10 inpatient records from the hospital were sampled randomly half a month in 2014. The records were reviewed to identify AEs according to the second edition of the IHI GTT for measuring AEs. Triggers and AEs were analyzed using Microsoft Excel 2007. Statistical analyses were performed using IBM SPSS software, version 19.0. Results: A review of 240 patient records identified 51.0% (26/51) triggers in the worksheet, and 33.3% (17/51) were associated with AEs. A total of 70 AEs were identified in 54 patients, including 65.7% (46/70) category E AEs, which represent temporary harm requiring intervention, and 34.3% (24/70) category F AEs, which represent temporary harm requiring initial or prolonged hospitalization. The average rate of AEs per 1000 patient-days was 32.1 ± 20.9. The average rate of AEs per 100 admissions was 29.2 ± 16.1. The average rate of admissions with an AE was 22.5% ± 13.9%. The most significant characteristic of patients with AEs was longer hospital stay. Conclusions: More than one fifth of adult inpatients in the current study experienced at least one AE resulting in temporary harm, most commonly caused by surgical operations and medication. With some modifications, the IHI GTT is a feasible and effective tool for detecting the overall status of AEs in a Chinese hospital.